Testing and Evaluation of a Smart Irrigation System towards Smart landscaping in UAE - ALSULAIMANI, FATMA (2017)
It is clear that the population is growing drastically causing an increase in urban development and landscape expansion which as a result increase the demand for water. In the GCC region, water is becoming a threat with the impact of climate change and the lack of water resources. The main source of water is mostly desalination plants. Irrigation system can reduce water consumption but the current system might not solve the issues of water in the near future. This study is an evaluation to the impact of an innovative technology, especially the use of Internet of things (IoT) on the performance of a typical irrigation system currently used in Dubai, UAE. A field experiment was conducted to measure the selected parameter: Water consumption and irrigation management. This means, a profound measurement on the impact of integrating soil moisture sensor into the current irrigation system is evaluated to assess the impact this integration. The research evaluates the environmental, economic and technical feasibility of the technology under UAE conditions. The core methodology used in this research was the field experiment; statistical analysis was also required to validate the results obtained on site. The results observed from the experiment were that the use of smart irrigation system (SIS) have an environmental advantages in the long term especially in terms of water consumption and irrigation management. Less water is required to irrigate when the soil is saturated enough causing a healthier plants growth. The outcomes of the use of SMS have shown a better results in water conservation and a decrease in water flow in the month of September by 21% and 26% in October. However, the economic analysis shows that the integration of soil moisture sensor isn’t viable in large field projects when heterogeneous soils covers large areas. The upfront cost is higher compared to the controlled irrigation system, yet the long term will have larger impact on the plantation growth and water conservation. Moreover, failing to choose the right depth in which moisture is contained and sensor is buried might cause a negative effect. Nevertheless, integrating new technologies in the irrigation system is a way to move smarter and innovative and this is what Dubai is moving towards.